2022
DOI: 10.1002/fft2.182
|View full text |Cite
|
Sign up to set email alerts
|

The microbial‐killing Ag nanoparticles in food supply chain: How it was applied and what a consumer should know?

Abstract: Moving to 133 years of the synthesis of citrate‐stabilized silver nanoparticles (AgNPs) by M. C. Lea (published in Am. J. Sci, 1889), a myriad of scholarly works and patents were published globally demonstrating the applicability of this microbial‐killing nanoparticles in various industries. One of the favorite applications is on the food supply chain whereby AgNPs serve to improve food safety and quality. In this paper, the adaptation of AgNPs in each phase of a typical food supply chain is disclosed, doubts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, the cost of nanotechnology adoption in food manufacturing and production is quite expensive which also comprises productivity, labour, and efficiency. Thus, the key factor determining whether or not a food manufacturer would adopt new technology is cost (Yeap et al, 2022). Previous research has found that price value is important in new technology adoption decisions and influences behavioural intentions to adopt new technology (Khan et al, 2022;Meng et al, 2023).…”
Section: Price Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cost of nanotechnology adoption in food manufacturing and production is quite expensive which also comprises productivity, labour, and efficiency. Thus, the key factor determining whether or not a food manufacturer would adopt new technology is cost (Yeap et al, 2022). Previous research has found that price value is important in new technology adoption decisions and influences behavioural intentions to adopt new technology (Khan et al, 2022;Meng et al, 2023).…”
Section: Price Valuementioning
confidence: 99%
“…From an academic standpoint, nanotechnology adoption in the food industry is limited in Malaysia in both scholar and practitioner contexts. A low rate of nanotechnology adoption and a lack of knowledge about the benefits of nanotechnology are factors influencing Malaysian nanotechnology adoption (Yeap et al, 2022). Furthermore, the lack of studies related to nanotechnology, particularly in the food industry from a consumer point of view, renders this field less investigated when compared to other technological advancement studies (Al-Waeli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%